Benzyl-2-Acetamido-2-Deoxy-α-d-Galactopyranoside Increases Human Immunodeficiency Virus Replication and Viral Outgrowth Efficacy In Vitro - Olvera, Alex; Martinez, Javier P.; Casadellà, Maria; Llano, Anuska; Rosás, Míriam; Mothe, Beatriz; Ruiz-Riol, Marta; Arsequell, Gemma; Valencia, Gregorio; Noguera-Julian, Marc; Paredes, Roger; Meyerhans, Andreas; et al. (Frontiers in Immunology, 2018)
Glycosylation of host and viral proteins is an important post-translational modification needed to ensure correct function of glycoproteins. For this reason, we asked whether inhibition of O-glycosylation during HIV in vitro replication could affect HIV infectivity and replication rates. We used Benzyl-2-acetamido-2-deoxy-α-D-galactopyranoside (BAGN), a compound that has been widely used to inhibit O-glycosylation in several cell lines. Pre-treatment and culture of PHA-blast target cells with BAGN increased the percentage of HIV infected cells (7.6-fold, p=0.0115), the per-cell amount of HIV p24 protein (1.3-fold, p=0.2475) and the viral particles in culture supernatants (7.1-fold, p=0.0029) compared to BAGN free cultures. Initiating infection with virus previously grown in the presence of BAGN further increased percentage of infected cells (30-fold, p<0.0001), intracellular p24 (1.5-fold, p=0.0433) and secreted viral particles (74-fold, p<0.0001). BAGN treated target cells showed less CD25 and CCR5 expression, but increased HLA-DR surface expression, which positively correlated with the number of infected cells. Importantly, BAGN improved viral outgrowth kinetics in 66% of the samples tested, including samples from HIV controllers and subjects in whom no virus could be expanded in the absence of BAGN. Sequencing of the isolated virus indicated no skewing of viral quasi-species populations when compared to BAGN-free culture conditions. BAGN also increased virus production in the ACH2 latency model when used together with latency reversing agents. Taken together, our results identify BAGN treatment as a simple strategy to improve viral outgrowth in vitro and may provide novel insights into host restriction mechanisms and O-glycosylation related therapeutic targets for HIV control strategies.